МORBIDITY OF INFLUENZA AND ACUTE VIRAL INFECTION IN YAKUTIA DURING EPIDEMIC SEASONS - I. Yu. Samojlova; S. I. Semenov; M. E. Ignat’eva; S. S. Shadrina; И. Ю. Самойлова; С. И. Семенов; М. Е. Игнатьева; С. С. Шадрина (Journal Infectology, 2018)
Objective: analysis of the incidence of SARS, influenza and determining the etiological structure of influenza in the Republic of Sakha (Yakutia), and in particular, in the Arctic zone of the Republic.Materials and methods: we used data from the official statistics of the national center for CPS, as well as summary data of the Federal center of Rospotrebnadzor. We analyzed the results of epidemiological survey (form 357/u) and laboratory tests. In the first season of the surveyed 1,140, in the II epidsezona – 3317 in the season – 3270. To determine circulating RNA of influenza virus of birds studied 1375 samples of wild and 958 samples in poultry.Results: the average incidence of Ari in the Republic of Sakha (Yakutia) for the period 2007–2016 significantly above the average for the same period the incidence in the Russian Federation. The incidence of SARS in some Arctic regions is considerably higher than the Russian and of the national average. The evolution over the last ten years the number of cases of influenza in the Republic varied greatly. In the Arctic regions of the Republic of the diagnosis of «influenza» over the entire period of observation were recorded in isolated cases. Was highly pathogenic strain of avian influenza A/wigeon/Sakha/1/2014 (H5N8).Conclusion: it is necessary to develop a network of interdistrict laboratories for the laboratory diagnosis of infectious diseases, equipping with modern equipment, developing a logistic scheme for the delivery of material for research with respect for transportation conditions, and training. Цель: проведение сравнительного анализа заболеваемости ОРВИ, гриппом на территории Республики Саха (Якутия) и в арктической зоне республики, а также определение этиологической структуры гриппа, других ОРВИ негриппозной этиологии.Материалы и методы: использованы данные официальной статистики Республиканского центра Роспотребнадзора, а также сводные данные Федерального центра Роспотребнадзора. Проанализированы результаты эпидемиологического обследования (форма 357/у) ...